2021
DOI: 10.1007/s00204-021-03123-y
|View full text |Cite
|
Sign up to set email alerts
|

Systems toxicology study reveals reduced impact of heated tobacco product aerosol extract relative to cigarette smoke on premature aging and exacerbation effects in aged aortic cells in vitro

Abstract: Aging and smoking are major risk factors for cardiovascular diseases (CVD). Our in vitro study compared, in the context of aging, the effects of the aerosol of Tobacco Heating System 2.2 (THS; an electrically heated tobacco product) and 3R4F reference cigarette smoke (CS) on processes that contribute to vascular pathomechanisms leading to CVD. Young and old human aortic smooth muscle cells (HAoSMC) were exposed to various concentrations of aqueous extracts (AE) from 3R4F CS [0.014–0.22 puffs/mL] or THS aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…A study from India in 699,686 women showed that the risk of multimorbidity was 87% higher in women who smoked or chewed tobacco and was 18% higher in those who consumed alcohol than in women who did not smoke or chew tobacco or consume alcohol, respectively 155 . Factors such as smoking promote cellular senescence through inflammatory effects, oxidative stress and DNA damage 156 , whereas exercise prevents cellular senescence 156,157 , highlighting the probable interplay between socioeconomic, psychosocial and behavioural determinants and the hallmarks of ageing.…”
Section: Allostasismentioning
confidence: 99%
“…A study from India in 699,686 women showed that the risk of multimorbidity was 87% higher in women who smoked or chewed tobacco and was 18% higher in those who consumed alcohol than in women who did not smoke or chew tobacco or consume alcohol, respectively 155 . Factors such as smoking promote cellular senescence through inflammatory effects, oxidative stress and DNA damage 156 , whereas exercise prevents cellular senescence 156,157 , highlighting the probable interplay between socioeconomic, psychosocial and behavioural determinants and the hallmarks of ageing.…”
Section: Allostasismentioning
confidence: 99%
“…Previous studies have demonstrated that aging-related senescence in vascular cells is responsible for AAA development in aging mice [ 33 ], which, combined with our results, could support the important role of cellular senescence in AAA formation. Notably, in contrast to age-related senescence, SIPS was closely associated with risk factors [ 13 ] for AAA, such as hypertension [ 10 ], hyperlipidemia [ 12 ] and cigarettes [ 11 ]. The above results indicated that SIPS might mediate the effect of risk factors on initiating the pathogenic process of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to risk factors for vascular diseases, such as hypertension [ 10 ], nicotine [ 11 ], and hyperlipidemia [ 12 ], promotes premature senescence in vascular cells by generating stress-dependent damage [ 13 ]. Stress-induced premature senescence (SIPS) has been found to be one of the main contributors to the formation of vascular diseases, including aortic atherosclerosis [ 14 ] and vascular calcification [ 15 ], indicating its relationship to AAA.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that there is a consensus about age-promoting properties of exposures to some compounds, also called “gerontogenic,” such as tobacco. Cigarette smoking has been involved with premature aging, accelerating aging, and, consequently, is a risk of age-related diseases and a link between cigarette smoking and cellular senescence has been widely raised ( Poussin et al, 2021 ). In accordance with our findings and hypothesis, Shi et al (2016) reported that miR-16-5p (a synonym of miR-15b-5p) had increased levels in plasma from healthy smokers, since miR-15b-5p (miR-16-5p is a synonym of miR-15b-5p) was the top one upstream regulator, indicating its potential role on several biological processes, including cell cycle deregulation.…”
Section: Discussionmentioning
confidence: 99%